Spectrum of Imaging Findings of Spinal Tuberculosis on Magnetic Resonance Imaging - Basam Pavani Reddy; K.S. Vedaraju (Asian Journal of Medical Radiological Research, 2022)
Background: To describe the spectrum of manifestations of spinal tuberculosis on Magnetic Resonance Imaging. To study the role of MRI in assessing the extent of disease and in the decision-making process. Subjects and Methods: It is a prospective study conducted at the department of Radiodiagnosis in Narayana Medical College and Hospital, Nellore. The study was carried out on 63 cases of spinal tuberculosis in the period of two years (August 2019 to august 2021). MRI features were observed on T1 Weighted, T2 Weighted and short tau inversion recovery (STIR) sequences. Diagnosis was based on the history, clinical features and characteristic radiological findings on MRI along with the response to the treatment. Results: Spinal tuberculosis was most commonly seen in young adults and of male predominance. Backache in 58(92%) and low-grade fever were found to be the most common clinical features followed by weight loss and paraparesis. Thoraco-lumbar spine was the most commonly involved in 26(41.2%), followed by thoracic, lumbar and sacral vertebrae. MRI findings included bone marrow edema in 63(100%), end plate irregularities in 63(100%), disc space reduction in 34(53.9%), pre and paravertebral collection in 26(41.2%), calcification in 25(39.6%), spinal cord compression in 18(28.5%). In patients with spinal cord compression exceeding more than 20%, neurological symptoms were seen. Vertebral body wedge collapse in 33(52.3%), compression fracture in 14(22.2%) and both vertebral body wedge collapse with compression fracture were noted in 5 (7.9%). Kyphotic deformity in 25 (39.6%) and scoliosis in 8(12.6%) was also noted. In the majority of cases, a paradiscal pattern of involvement was found. Conclusion: Spinal tuberculosis is best evaluated on the Magnetic Resonance Imaging as it provides valuable and critical information regarding the spectrum, ranging from simple edema involving the vertebrae, intervertebral discs to the paraspinal collections, abscesses and vertebral collapse leading to spinal cord compression in patients with neurological deficit and thereby limiting the morbidity and helping in early diagnosis and guiding the management.